ANALISIS PENGARUH INVESTMENT OPPORTUNITY SET, FIRM SIZE DAN PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN - Ach Taufiqur Rohman; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis research aims to know the relationship of Investment Opportunity Set, Firm Size and profitability against the dividend policy. The type of research used is explanatory research. The data used are secondary data, obtained with the technique of documentation from website BEI. The population which becomes the object of this study is that companies in the manufacturing sector were listed on the Indonesia stock exchange period 2016-2017. The selection of the sample using the technique of purposive sampling, so obtained 55 companies. Technique of data analysis in this study uses the test of normality, test the assumptions of classical, linear multiple regression test and test hypotheses. Measuring instrument used Investment Opportunity Set is a Book to Market Equity, for Firm Size using gauge total assets, and to measure the profitability of using Return On Equity, while tools measure used to gauge the Policy Dividend is a Dividend Payout Ratio. The results showed that: (1) Investment Opportunity Set of positive effect significantly to dividend policy, (2) Firm Size effect positively not significantly to dividend policy, while (3) The negative effect was not significant profitability against the dividend policy. Keywords: Investment Opportunity Set, Firm Size, Profitability, and Dividend Policy